Draft Genome Sequence of a Novel Coriobacteriaceae sp. Strain, EMTCatB1, Reconstructed from the Metagenome of a Thermophilic Electromethanogenic Biocathode - Kobayashi, Hajime (Genome Announc, 2017)
A draft genome of Coriobacteriaceae sp. strain EMTCatB1 was determined through taxonomic binning of a metagenome of a thermophilic biocathode actively catalyzing electromethanogenesis. This genome will provide information about the biocathode ecosystem, as well as the natural diversity of the Coriobacteriaceae family.